2021
DOI: 10.32641/andespediatr.v92i1.1628
|View full text |Cite
|
Sign up to set email alerts
|

Función pulmonar evolutiva evaluada por oscilometría de impulso en prescolares con asma

Abstract: La oscilometría de impulso (IOS) es útil para evaluar la función pulmonar en preescolares.Nuestro objetivo fue describir las alteraciones y perfil evolutivo de la IOS en asmáticos menores de 6 años luego de un año de seguimiento.Pacientes y Método: 62 preescolares realizaron IOS al inicio del estudio y luego de un año. Se comparó la proporción de IOS alterada y respuesta broncodilatadora (RB+) en ambos tiempos, además de subanálisis según control de asma y presencia de atopía. Para el análisis estadístico se u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…10 Previously, we studied the evolution of lung function, measured by IOS, over a period of 1 year, in preschool children with moderate to severe persistent asthma and found that in a high percentage of them it was altered, and although some parameters improved, others showed a persistent alteration. 11 Therefore, we believe it is important to establish if alterations in IOS in preschool children are associated with having an altered spirometry at school age.…”
mentioning
confidence: 99%
“…10 Previously, we studied the evolution of lung function, measured by IOS, over a period of 1 year, in preschool children with moderate to severe persistent asthma and found that in a high percentage of them it was altered, and although some parameters improved, others showed a persistent alteration. 11 Therefore, we believe it is important to establish if alterations in IOS in preschool children are associated with having an altered spirometry at school age.…”
mentioning
confidence: 99%